TINJAUAN KEBUTUHAN WISATAWAN DI OBJEK WISATA PANTAI PADANG - Zuhra, Usie Fatimah; Chair, Ira Meirina; Kasmita, Kasmita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This study aimed to describe about travelers needs in Padang Coast Attractions in the review: physiological needs, safety needs, social needs, esteem needs and self-actualization needs.This type of research is descriptive with qualitative data.Data collection techniques by using interviews, observation, and documentation.Based on the research it about the needs of travelers in Padang Beach Attractions namely: physiological needsa clean place to eat and have facilities such as bathrooms, as well as a place to wash hands, gazebo that is safe, comfortable, and clean, the bathrooms are clean, mosquito. Safety needs security officers,parking attendantsand also life guard. Social needs a place to sit and a playground for children. Esteem needs merchands and beach officer more appreciative tourists who come to Padang beach. Self-actualization needs water sports, entertainment and race event held at Padang Beach. Key Word: Needs, Coast Attractions